Enhancement of immunogenicity of SARS-CoV-2 spike protein expressed in Escherichia coli by fusion of the CRM197 functional domain - Yu, Xibing; Yang, Yinmeng; Zhang, Miao; Shen, Qiantong; Zhu, Yun; An, Tong; Li, Siqi; Zhang, Kexin; Lu, Shuaiyao; Lu, Shaohong; Zhuang, Fangcheng; Gao, Meng (Frontiers in Microbiology, 2025)
As an immunogenic non-toxic mutant of diphtheria toxin (DT), cross-reacting material 197 (CRM197) exhibits a significant immunogenicity-enhancing effect on various pathogenic vaccines. However, its application in vaccines against highly pathogenic pathogens remains underexplored. In this study, we incorporated CRM197 into a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine, aiming to identify a molecular adjuvant capable of inducing broad-spectrum neutralizing antibodies and to develop a subunit vaccine with stronger cross-reactivity, improved safety, and greater accessibility. Our findings revealed that compared to non-fused SARS-CoV-2 spike (S) protein receptor-binding domain (RBD) (designated sRBD), the fusion of CRM197 with the SARS-CoV-2 S protein RBD (termed CRM-RBD) elicited stronger humoral immunity, Th1-biased cellular immune responses, and reduced immune evasion against SARS-CoV-2 variants in mice. Furthermore, mice immunized with CRM-RBD exhibited significantly lower mortality and reduced pulmonary pathology upon viral challenge. These results demonstrate that CRM197 substantially enhances the immunogenicity of SARS-CoV-2 vaccines, positioning it as an ideal candidate protein for developing SARS-CoV-2 vaccines with broader cross-reactivity.